2021
DOI: 10.1155/2021/6694594
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Activity on Oxidative Stress Markers in Patients with Metastatic Breast Cancer

Abstract: Purpose. Regular physical activity (PA) can affect oxidative stress, known to be involved in carcinogenesis. The objective of this study was to evaluate the associations between a six-month PA intervention and oxidative stress biomarkers, PA, and clinical outcomes in patients with metastatic breast cancer. Methods. Forty-nine newly diagnosed patients with metastatic breast cancer were recruited for a single-arm, unsupervised, and personalized six-month walking intervention with activity tracker. PA level and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…It is reported that the generation of MDA can aggravate the damage of the cell membrane and also reflect antioxidant capacity 38,39 . Change in inflammatory cytokines may be a downstream process of increased MDA production in the normal tissues of the CONV group.…”
Section: Discussionmentioning
confidence: 97%
“…It is reported that the generation of MDA can aggravate the damage of the cell membrane and also reflect antioxidant capacity 38,39 . Change in inflammatory cytokines may be a downstream process of increased MDA production in the normal tissues of the CONV group.…”
Section: Discussionmentioning
confidence: 97%
“…These data are intriguing in the context of the clinical management of BC patients since the widely noted role of inflammation in the complex process underpinning oncogenesis and cancer growth promotion ( Mahadevan and Zanetti, 2011 ; Koelwyn et al, 2015 ). In addition, strong evidence supported the role of physical exercise in increasing the overall survival of BC patients, probably due to its effects on oxidative stress and inflammation ( Saarto et al, 2012 ; Winters-Stone et al, 2013 ; Wennerberg et al, 2020 ; Delrieu et al, 2021 ; Vehmanen et al, 2021 ; Longobucco et al, 2022 ). Therefore, these biomarker modifications might be the basis for a more precise exercise prescription aiming at reducing systemic inflammation in BC survivors in order to reduce tumor growth or risk of recurrence.…”
Section: Discussionmentioning
confidence: 98%
“…Plasma antioxidant activity (plasma superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPX)), and markers of oxidative stress damage (advanced oxidation protein products (AOPP), and malondialdehyde) were determined as previously described ( Delrieu et al, 2021 ) (Delrieu et al, Oxidative Medicine and Cellular Longevity 2021).…”
Section: Methodsmentioning
confidence: 99%